Conduction system pacing in cardiac resynchronization: short-mid term follow-up. (14th October 2021) - Marcantoni, L; Pastore, G; Baracca, E; Pellegrini, N; Bartolomei, M; Andreaggi, S; Galuppi, E; Centioni, M; Rigatelli, G; Roncon, L; Zanon, F
Abstract: Background: Conduction system pacing (CSP) includes both His Bundle Pacing (HBP) and left bundle branch pacing (LBBP). It engages the conduction system ensuring synchronous activation of ventricles, potentially acting as cardiac resynchronization. Purpose: The aim of the study is to report technical and clinical outcomes of CSP (HBP or LBBP) utilized in patients referred for cardiac resynchronization therapy. Methods: CSP was applied in 51 patients (mean age 75±9 years; 47 males) referred for cardiac resynchronization therapy. 41 cases were de-novo implant and 10 were up-grading after PICM. Ischemic aetiology was present in 23 (45%) patients, hypertension in 31 (61%); diabetes in 19 (37%), severe kidney disease in 4 (8%). Devices were checked 48 hours and 1 month after implant and then remotely. Clinical, echocardiographic, electrocardiographic data were also collected. Results: Conduction system pacing was successfully obtained in 45 (88.3%) patients. In 28 (62%) cases the lead was implanted in the His Bundle and in 17 (38%) in the left bundle. In 6 (11.7%) patients it was not possible to fix the lead in the His Bundle neither in the Left bundle, in these cases a standard quadripolar lead in the coronary sinus was implanted. In 28 (62%) patients was utilized the 3830 4 Fr lumen-less lead and in the remaining 17 (38%) cases a standard stylet-driven lead. Basal mean EF was 33±9% and improved to 42±9% (P<0.005) after a mean follow-up of 266±212 days. Baseline QRSd narrowed from 168±35 ms to135±12 ms. Four (8.8%) patients were hospitalized due to HF symptoms (in 2 cases fast AF was recorded and treated with AV nodal ablation, in 2 cases significant mitral regurgitation). Conclusions: Conduction system pacing can act effectively as cardiac resynchronization in patients with severe cardiac disfunction and bundle branch block with high success rate, significantly narrowed QRS and improved EF at short-medium term follow-up. Funding Acknowledgement: Type of funding sources: None.